Perinatal and neonatal outcomes of pregnancies after early rescue intracytoplasmic sperm injection in women with primary infertility compared with conventional intracytoplasmic sperm injection: a retrospective 6-year study - Feng Xiong; Qing Sun; Guangui Li; Zhihong Yao; Peilin Chen; Caiyun Wan; Huixian Zhong; Yong Zeng (BMC, 2020)
Abstract Background Early rescue intracytoplasmic sperm injection (ICSI) has been used in clinic as appropriate currently. While the outcomes of children born after this method were not well assessed. The purpose of this study was to evaluate the effect of early rescue ICSI on women with primary infertility. Methods Fresh embryo transfer cycles after rescue (n = 214) and conventional (n = 546) ICSI were retrospectively evaluated from women with primary infertility who underwent their first assisted reproductive technology cycles at our center in 2012-2017. The conventional ICSI group was subdivided into ICSI-1 (semen suitable for in vitro fertilization, IVF) and ICSI-2 (poor semen quality) to minimize bias from differences in semen quality. Pregnancy, delivery and neonatal outcomes were compared between groups. Results There was a higher rate of polyspermy and a lower rate of top-quality embryos (TQE) on day 3 for oocytes subject to rescue ICSI compared with conventional ICSI. This reduced the total number of TQE and the number of TQE transferred in the rescue ICSI group. There was no significant difference between groups in clinical pregnancy, ongoing pregnancy, early miscarriage and live birth. For pregnant women, gestational age, route of delivery, risk of preterm birth and gestational diabetes mellitus were also comparable. Neonatal outcomes including sex ratio, birth weight, neonatal intensive care unit admission and birth defects were also similar after rescue and conventional ICSI. Moreover, no differences were observed with the different ICSI subgroups. Conclusions For women with primary infertility who have a high risk of IVF fertilization failure (FF), rescue ICSI provides a safe and efficient alternative to minimize FF after initial IVF, but results in fewer TQE on day 3.